Impact of the Aortomitral Positional Anatomy on Atrioventricular Conduction Disorder Following Mitral Valve Surgery - Kazuma Handa; Masashi Kawamura; Daisuke Yoshioka; Shunsuke Saito; Takuji Kawamura; Ai Kawamura; Yusuke Misumi; Masaki Taira; Kazuo Shimamura; Sho Komukai; Tetsuhisa Kitamura; Shigeru Miyagawa (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Variations in the aortomitral positional anatomy, including aortic root rotation appear to be related to variations in the location of the conduction system, including the bundle of His. However, little is known about their clinical significance. Methods and Results This study included 147 patients with normal ECGs who underwent mitral valve surgery. The aortomitral anatomy was classified using preoperative 3‐dimensional transesophageal echocardiography, and postoperative conduction disorders, including atrioventricular block and bundle branch block, were analyzed. Variations classified as aortomitral appearance were designated as having a center appearance (85.7%, n=126/147) or lateral appearance (14.3%, n=21/147) on the basis of whether the aortic root was located at the center or was shifted to the left fibrous trigone side. Subsequently, those with a center appearance, aortic root rotation was classified as having a center rotation (83.3% [n=105/126]), in which the commissure of the left and noncoronary aortic leaflet was located at the center, lateral rotation (14.3% [n=18/126]), rotated to the left trigone side, or medial rotation (2.4% [n=3/126]), rotated to the right. The incidence of 3‐month persistent new‐onset conduction disorder was higher in the lateral appearance than the center appearance group (21.1% versus 5.0%; P=0.031) and higher in the lateral rotation than in the center or medial rotation groups (29.4% versus 1.0% versus 0.0%, respectively; P<0.001). Conclusions Aortomitral variations can be classified using 3‐dimensional transesophageal echocardiography. Lateral appearance and lateral rotation are risk factors for conduction disorders in mitral valve surgery.